Empowering Scientific Inquiry Literacy Through SIDILAN: A Dissemination Program for Elementary School Teachers - Dina Rahmi Darman; Firmanul Catur Wibowo; Imaningtyas; Nina Nurhasanah; Linda Zakiah; Mira Amelia Amri; Endang M. Kurnianti; Endang Wahyudiana; Indah Wardatussa’idah; Chrisnaji Banindra Yudha (Research and Social Study Institute, 2025)
Background: The lack of science inquiry literacy among elementary school teachers is a crucial issue affecting the quality of science education. This condition is caused by various factors, including low teacher LIS competency, inadequate facilities, and a lack of learning media that support inquiry learning for students' diverse learning styles. To address this, training is needed that can provide teachers with opportunities to design inquiry learning based on students' learning styles.Aims and Method: This community services program aimed to enhance teachers' Scientific Inquiry Literacy (SIL) through the dissemination of SIDILAN using the Interactive Lecture Demonstration method.Results: The pre-posttest results showed a high average N-Gain (0.76), categorized as High. 13 teachers who were drilled using the SIDILAN application in their lessons experienced an increase in SIL knowledge, categorized as High. Two teachers also experienced an increase in SIL knowledge, categorized as Medium. . There has been an increase in teachers' knowledge about SIL, student learning styles, the relationship between SIL and learning styles, and scientific inquiry learning designs that facilitate various student learning styles. Teachers reported SIDILAN as user-friendly, effective in identifying student learning styles, useful for instructional planning. and improving inquiry skills so that they could achieve science with good inquiry.